THE EFFECT OF QARDH FINANCING ON BUSINESS STABILITY AND SUSTAINABILITY OF MSME FINANCIAL INCLUSION - Nurul Jadid; Abdullah Ahadish Shamad; Tanbihul Ghofilin (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2026)
Qardh financing in Islamic microfinance institutions has not been widely supported by strong empirical evidence regarding its effectiveness in enhancing the stability and sustainability of MSME businesses. This study aims to examine the effect of Qardh financing on business stability and sustainability among MSME members of BMT Maslahah Surabaya Branch. The quantitative research method involved 83 MSME members as respondents. The results indicate that Qardh financing has a positive and significant effect on business stability and sustainability. The Adjusted R Square value of 0.574 shows that Qardh financing explains 57% of the variation in MSME business stability and sustainability. This finding contributes to the development of Islamic social finance literature by examining the strategic role of Qardh in enhancing micro-enterprise resilience. Practically, it provides policy implications for BMT institutions and Islamic financial inclusion strategies, emphasising Qardh financing as an effective instrument to support sustainable MSME development.